Kontribusi Semiotika dalam Memahami Bahasa al-QurâÃ¢n - Muzakki, Akhmad (ISLAMICA: Jurnal Studi Keislaman, 2009)
The texts of the QurâÃ¢n may be understood as a collection of symbols, and cannot be interpreted in isolation from the context as their background. If semiotics is a science of symbols, then the texts of the QurâÃ¢n must be the fertile object for the study of semiotics. In the science of semiotics, texts are deemed to have no end in themselves, meaning that we must not acknowledge them as having ended or being finalized at some point. Some philosophers such as Jacques Derrida have underscored this, and maintained that language is a metaphor. A meaning that we assume resulted from our use of language is in fact the product of the metaphorical exchange. Hence, a meaning will change as soon as the subject of the metaphorical exchange changes. Meaning in other words is both dynamic and relational because it is based on an endless source.